PRACTICAL RELEVANCE OF IMPAIRED WATER AND SALT METABOLISM IN PATIENTS WITH HEART FAILURE - Shakhobidinov X.Sh.; Usmanova D.N.; Bektasheva G.M (Scholar Express Journals, 2023)
A prospective study was conducted with the participation of 396 patients hospitalized for decompensation of chronic heart failure. Hyponatremia was diagnosed with a decrease in serum sodium
Keywords: hyponatremia; chronic heart failure; decompensation; severity of the disease